Active airflow of the paranasal sinuses in extinct crocodyliforms: Evidence from a natural cast of the thalattosuchian Dakosaurus andiniensis - Fernández, Marta S. (2021)
The evolution of Thalattosuchia documents the unique shift among Crocodylomorpha from aquatic continental/coastal habitats to a fully pelagic lifestyle. This transition was coupled with deep modification of their skeletons, such as hydrofoil forelimbs, hypocercal tail, and loss of osteoderms. The natural snout casts of the rhacheosaurin Cricosaurus araucanensis showed that it also included changes in the internal anatomy of the snout like the enlargement of nasal glands (probably for salt excretion) and the rearrangement of the paranasal sinus system, including the internalization of the antorbital sinus. Here we described the snout natural cast of the geosaurin Dakosaurus andiniensis from the Late Jurassic of Patagonia. The information provided by it indicates that, despite having different external morphologies and ecology, D. andiniensis and C. araucanensis share the same facial anatomy. The new cast preserves a suborbital diverticulum of the antorbital sinus protruding into the orbit through the postnasal fenestra. Its location indicates that it was interleaved with jaw adductor muscles suggesting an active airflow in the paranasal sinus. We provide a putative functional interpretation of this peculiar arrangement where bellow pumps actions of musculature may help drain salt glands. The rearrangement of the paranasal sinuses predates the transition to a completely pelagic-lifestyle. We proposed a stepwise evolutionary scenario of Thalattosuchia, implying changes in the preorbital region (and orbit orientation) where the internalized antorbital sinus via its subsidiary diverticulum was co-opted for helping nasal glands drainage. Further scrutiny of facial anatomy of a larger sample of thalattosuchians will help to test this hypothesis.